Prevalence of Thyrotoxicosis, Antithyroid Medication Use, and Complications Among Pregnant Women in the United States - Korelitz, James J. (Mary Ann Liebert, Inc., 2013)
BACKGROUND: Population-based estimates of the prevalence of thyrotoxicosis (TTX), the frequency of antithyroid drug (ATD) use, and risk of adverse events in pregnant women and their infants are lacking. Therefore, our objective was to obtain epidemiologic estimates of these parameters within a large population-based sample of pregnant women with TTX. METHODS: A retrospective claims analysis was performed from the MarketScan Commercial Claims and Encounters health insurance database for the period 2005–2009. Women aged 15–44 years, enrolled for at least 2 years, and who had a pregnancy during the study period were included. Diagnosis of TTX was based on International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes using narrow (TTX-1=ICD 242.0) and broad (TTX-2=ICD 242.0 or 242.9) definitions. ATD use was based on prescriptions filled for propylthiouracil (PTU) or methimazole (MMI). Adverse events in mothers and infants were determined from the ICD-9-CM diagnosis codes recorded on submitted claims. RESULTS: The database contained 904,497 eligible women. The average yearly prevalence per 1000 pregnant women was 2.46 for TTX-1 and 5.88 for TTX-2. Thirty-nine percent used ATD at any time during the study period. Compared to women without a TTX diagnosis, there was more than a twofold increase for liver disease among women with TTX (odds ratio [OR]=2.08, p<0.001) and a 13% increased risk for congenital anomalies (OR=1.13, p=0.014), but no association was observed with ATD use. The rates of congenital defects (per 1000 infants) associated with ATD use were 55.6 for MMI, 72.1 for PTU, and 65.8 for untreated women with TTX, compared to 58.8 among women without TTX. CONCLUSIONS: There was some indication of an elevated risk of liver disease and congenital anomalies in women with TTX, but the risk did not appear to be related to the ATD use. There seems to be a higher pregnancy termination rate for women with TTX on MMI, which likely reflects elective pregnancy terminations.